123/125I-labelled 2-iodo-L: -phenylalanine and 2-iodo-D: -phenylalanine: comparative uptake in various tumour types and biodistribution in mice. - Kersemans, V; Cornelissen, B; Kersemans, K; Bauwens, M; Dierckx, R; De Spiegeleer, B; Mertens, J; Slegers, G (2006)
PURPOSE: In vitro in the R1M cell model and in vivo in the R1M tumour-bearing athymic model, both [(123)I]-2-iodo-L: -phenylalanine and [(123)I]-2-iodo-D: -phenylalanine have shown promising results as tumour diagnostic agents for SPECT. In order to compare these two amino acid analogues and to examine whether the observed characteristics could be generalised, both isomers were evaluated in various tumour models. METHODS: Transport type characterisation in vitro in A549, A2058, C6, C32, Capan2, EF43fgf4, HT29 and R1M cells with [(123)I]-2-iodo-L: -phenylalanine was performed using the method described by Shotwell et al. Subsequently, [(123)I]-2-iodo-L: -phenylalanine and [(123)I]-2-iodo-D: -phenylalanine tumour uptake and biodistribution were evaluated using dynamic planar imaging and/or dissection in A549, A2058, C6, C32, Capan2, EF43fgf4, HT29 and R1M inoculated athymic mice. Two-compartment blood modelling of the imaging results was performed. RESULTS: In vitro testing demonstrated that [(123)I]-2-iodo-L: -phenylalanine was transported in all tumour cell lines by LAT1. In all tumour models, the two amino acid analogues showed the same general biodistribution characteristics: high and specific tumour uptake and renal tracer clearance. Two-compartment modelling revealed that the D: -isomer showed a faster blood clearance together with a faster distribution to the peripheral compartment in comparison with [(123)I]-2-iodo-L: -phenylalanine. CONCLUSION: [(123)I]-2-iodo-L: -phenylalanine and its D: -isomer are promising tumour diagnostic agents for dynamic planar imaging. They showed a high and similar uptake in all tested tumours. [(123)I]-2-iodo-D: -phenylalanine showed better tracer characteristics concerning radiation dose to other organs.